FEM Analysis Applied to OT Bridge Abutment with Seeger Retention System - Cervino, Gabriele (Eur J Dent, 2021)
Objective  The purpose of this investigation is to highlight the technical components of a new kind of screw-retained dental implant prosthesis. The hypothesis is whether the OT Bridge (Rhein 83 S.R.L.; Bologna, Italy) system could be applied without secondary screw in the “all-on-four” retention system, thanks to the presence of an internal seeger. Materials and Methods  By using engineering device such as finite element method (FEM) and von Mises investigation, it has been studied how the fixed prosthodontics for full-arch retention can be influenced by the presence of the screw for stabilizing it. Results  In a dental implant, one model with four different configurations of the full-arch prosthesis retainer and the seeger has been investigated and then examined in contrast with or without the passant screw for locking the system. The experiments of this virtual study highlighted different features and mechanical behaviors of prosthodontic attachments. Conclusion  The first two configurations, respectively those in which there are four and three connection screws, are safe and predictable. Therefore, the presence of the seeger significantly improves the stability and the retention of the whole prosthesis.